Correlation of Rehabilitation and Throwing Program Milestones With Outcomes After Ulnar Collateral Ligament Reconstruction: An Analysis of 717 Professional Baseball Pitchers. Issue 7 (June 2022) - Griffith, Timothy B.; Conte, Stan; Poulis, George C.; Diamond, Adam; D'Angelo, John; Camp, Christopher L.
Background: There remains room for improvement in surgical outcomes after medial ulnar collateral ligament reconstruction (MUCLR) in professional pitchers. The role and influence of postoperative rehabilitation on the outcomes of MUCLR are unknown. There is a paucity of clinical data in the current literature comparing the success of various postsurgical rehabilitation protocols after MUCLR. Purpose: To summarize the current rehabilitation process for professional pitchers recovering from MUCLR, evaluates what player and surgical factors correlate with outcomes, and determines whether rehabilitation timing and milestones correlate with successful outcomes. Study Design: Case series; Level of evidence, 4. Methods: 717 professional baseball pitchers who underwent MUCLR between 2010 and 2016 were identified and included in the analysis. Player characteristics evaluated included age at the time of surgery, throwing side dominance, primary pitching role (starter vs reliever), and level of play (MLB, AAA, AA, A). Surgical factors studied included date of surgery, graft type (palmaris longus autograft vs gracilis autograft), and surgical technique (figure of 8 vs docking vs other). The rehabilitation and throwing progression details were as follows: initiation date; first throw date; dates to start throwing from various distances; longest distance thrown; first flat ground throw date; first mound throw date; and first live batting practice (BP) date. The primary outcomes of interest were the ability to return to play at any level (RTP), the ability to return to the same level (RSL), and the time to RTP/RSL. Results: On average, pitchers threw a baseball for the first time 4.9 months after surgery, with a broad range (2.8-14.9 months). For the 675 (94%) pitchers who were able to progress to mound throwing, the first throws off a mound occurred at a mean of 9.4 months after surgery. Before progressing to the mound, the mean longest long-toss distance reached was 137.5 feet, with a broad range (105-300 feet). A high variation in the time to RTP (7.6-53.9 months) and RSL (8.6-60.7 months) was noted. A total of 599 (84%) pitchers were able to RTP at a mean time of 14.9 ± 4.9 months after surgery (range, 7.6-53.9 months). Also, 528 (74%) pitchers were able to RSL after MUCLR at a mean of 17.4 ± 7 months (range, 8.6-60.7 months) postoperatively. Age was the most significant predictor of RTP (hazard ratio [HR], 1.03 [95% CI, 1.01-1.05]; P = .01) and RSL (HR, 0.96 [95% CI, 0.93-0.99]; P < .01). For every 1-year increase in age, there was a 3% increase in the chance of RTP. Conversely, for every 1-year decrease in age, there was a 4% increase in the chance of RSL. MLB players were more likely to RTP (HR, 1.39 [95% CI, 1.18-1.63]; P < .01) but not necessarily to RSL (HR, 0.90 [95% CI, 0.75-1.08]; P = .24). The time from surgery to any of the rehabilitation milestones of interest (first throw, first flat ground pitching, first mound throwing, and first live BP) did not correlate with RTP or RSL (all, P >.05). The same was true for the greatest long-toss distance thrown before transitioning to the mound. Conclusion: Significant variability in the postoperative rehabilitation protocols after MUCLR was observed in 717 professional baseball pitchers. The timing of achievement of throwing progression and rehabilitation milestones postoperatively varied widely but did not correlate with outcomes. Player characteristics—except for player age and professional pitching level—did not correlate with RTP and RSL outcomes. Older pitchers and MLB pitchers were more likely to RTP, but younger players were more likely to RSL. Surgical factors did not correlate with rehabilitation outcomes.